OPTIMIZING ONLINE MEDIA IN PROMOTION OF MARINE TOURISM IN GILI NANGGU - Sutama, I Wayan (Institut Agama Hindu Negeri Gde Puda Mataram, 2024)
The dynamics and development of the tourism industry in the global era promises opportunities for other fields to develop. With the aim of maximizing the use of online media in the tourism industry, especially Gili Nanggu destination objects, this paper seeks to explore various destination promotion and marketing strategies that can increase tourist visits. Using a qualitative approach with single-object case studies and statistical data analysis in online media, this paper concludes the importance of local government support in the development of Gili Nanggu tourism and surrounding islands through regulations based on integrated destination sustainability and oriented towards efforts to increase local native income such as promoting the surrounding area through ease of investment for the private sector. The importance of synergy of cooperation with the private sector in designing sustainable tourism destination development is a homework with the government and all stakeholders involved. In addition, to attract more visitors, promotional objectives must be expanded such as efforts to save the environment and tourism sustainability continue to be echoed by involving endowsers or influencers to lift the image of the destination through optimization online media.